Various Comparisons of White Sticky Rice with Red Rice Toward the Volume of Brem Drink and Organoleptic Test Tape Foods - Widiyanti, Ni Luh Manik; Sukarta, I Nyoman (Universitas Pendidikan Ganesha, 2022)
The effect of the nutritional value of red rice tape is mainly different in fiber and antioxidant content, with sticky rice tape as a new health food innovation. The purpose of this study was to make a tape food by comparing glutinous rice with brown rice to the volume of brewed brem and the organoleptic test of tape food. This study used 3 designs: an accurate experimental study for the treatment of red rice tape on the volume of brem drinks; an experimental quasi for measuring organoleptic and hedonic test scores; and a pre-experiment for the number of panelists. Collecting data from the volume of brem drinks and organoleptic and hedonic tests. Analysis of the volume of brem drinks due to treatment using ANOVA and if there is a significant difference analyzed by LSD test using post hoc test. Organoleptic and hedonic tests were performed to determine the score of each organoleptic and hedonic test by the panelists. The ANOVA analysis of the production volume of Brem drinks from the three treatments showed significant differences. The results of the LSD test showed that the variation of the ratio of glutinous rice: to brown rice 3:1 was significantly different in the 1:1 treatment and the 1:3 treatment. The treatment of the ratio of glutinous rice: brown rice 1: 1 was not significantly different from the comparison treatment of glutinous rice: brown rice 1:3. Organoleptic and hedonic tests, as well as characteristics produced from red rice tape, were evaluated by organoleptic and hedonic test scores.